Pemanfaatan Kredit Usaha Rakyat oleh Peternak Sapi Potong di Kabupaten Lampung Tengah, Lampung - Ilham, Nyak; Gunawan, Endro; Syukur, Mat; Suhartini, Sri Hastuti (Analisis Kebijakan Pertanian, 2023)
To increase technology adoption and business scale in beef cattle farming, financing that is easily accessible to farmers is needed. One form of government support for providing funding sources is a Bank Loans for Farmers program called the Kredit Usaha Rakyat (KUR) scheme. This study aims to identify the business process of KUR distribution and repayment and also analyze the factors that influence the use of KUR by beef cattle farmers. This research was conducted in 2020 in Central Lampung Regency, Lampung Province. The number of respondents was 71 people, consisting of breeders, KUR's distributors, and related service officers. Data was collected through interviews and Focused Group Discussion (FGD) and analyzed using the logit model. The results of the study conclude that: (i) the KUR service business process continues to improve from time to time, but the implementation still has some obstacles, and (ii) the farmer's decision to use the KUR is strongly influenced by the terms and procedures of the KUR's distributor. Therefore, to encourage the creation of independent farmers in financing their businesses, it is necessary to review the payback period and the amount of the ceiling loan on cattle breeding and fattening businesses. Another recommendation is to reduce the gap between the guidelines issued by the KUR's Committee and the implementation of KUR by KUR's Distributors in fields through socialization, promotion, and advocacy.
Keywords: beef cattle; farmer; logit model; KUR; technology adoption